Bibliographies Made Easy: A Guide to Using Citation Software to Create Bibliographies. Issue 17 (21st September 2018) - Vivek, S.; Leblanc, S.
Abstract: Managing references, inserting citations, and creating bibliographies take a considerable amount of our time in the academic world. Tools are now available in the form of citation software that can easily help us produce highly professional bibliographies easily. This article provides a beginners guide to such software with tips on using them effectively. © 2018 by John Wiley & Sons, Inc.